Topical issues of systems engineering - Gusakov, Alexander; Ilina, Olga; Kulikova, Ekaterina; Melikhova, Olga (Journal of Civil Engineering and Management, 2003)
The article deals with topical issues of systems engineering development which is considered as a scientific-engineering methodology of effective design and functioning of construction systems and intersystem ties that are of great diversity and individuality. The authors investigate the processes of forming and selecting CAD information strategies, norms- and rule-making in construction sphere, methods of macrodesign of construction systems.First Published Online: 26 Jul 2012